Forest Fire Simulation in High Performance Computing - Denham, Mónica Malén (2021)
This work presents a research line related to the simulation of wild fires. It is being developed in San Carlos de Bariloche, Rio Negro, Patagonia Argentina. Our multidisciplinary team is composed by computer scientists, physicists, atmospheric and biological scientists and electronic engineers, coming from different institutions: CONICET, Universidad Nacional de Río Negro, Centro Atómico Bariloche, Universidad Nacional del Comahue. As a result of this interaction we’ve developed a forest fire simulator with a visual interface that allows to test different scenarios for fire propagation. The application is tailored according to the needs of local firefighters with whom we define the main features needed to eventually use our simulator for management purposes.